Detection of rabies virus via exciton energy transfer between CdTe quantum dots and Au nanoparticles - Liao, Yan-Juan; Li, Duo-Duo; Cai, Zong-Ling; Cao, Ying; Yu, Dong-Ling; Zhang, Hong-Yun; Kiflu, Abraha Bahlbi; Huang, Zai Yin; Li, Xiao-Ning; Luo, Ting Rong (Frontiers in Veterinary Science, 2022)
Rabies is a fatal encephalitis caused by the rabies virus. The diagnosis of the disease depends in large part on the exposure history of the victim and clinical manifestations of the disease. Rapid rabies diagnosis is an important step in its prevention and control. Therefore, for accurate and timely diagnosis and prevention of rabies, we developed nanomaterials for a novel photoelectrochemical biosensing approach (PBA) for the rapid and reliable diagnosis of rabies virus. This approach uses high-efficiency exciton energy transfer between cadmium telluride quantum dots and Au nanoparticles and is low cost, and easy to miniaturize. By constructing PBA, rabies virus can be detected quickly and with a high degree of sensitivity and specificity; the minimum detection concentration limit for rabies virus is approximately 2.16 ffu/mL of rabies virus particles, or 2.53 × 101 fg/mL of rabies virus RNA. PBA could also detect rabies virus in the brain and lung tissue from rabid dogs and mice with better sensitivity than RT-PCR.